The 2004 hurricanes in the Caribbean and the tsunami in the Indian Ocean : lessons and policy changes for development and disaster reduction - Martí, Ricardo Zapata (CEPAL SantiagoCL, 2005)
Looks at the differentiated impact that recent events such as the tsunami and hurricanes have on different countries, sectors, communities and localities. Provides examples, going into some detail on the 26 December tsunami. Tackles the impact of the 2004 hurricane season in the Caribbean. Provides conclusions and possible policy proposals.